Exercise and nutrition strategies for sarcopenia in older adults: evidence from a network meta-analysis based on EWGSOP and AWGS criteria - Zhao, Rongting; Dong, Yangjian; Zheng, Quansheng; Yao, Jiwei (Frontiers in Nutrition, 2025)
ObjectivesThis network meta-analysis aimed to evaluate the comparative effectiveness of different exercise and nutritional interventions on muscle strength, skeletal muscle mass, and physical function in older adults with sarcopenia diagnosed according to the European Working Group on Sarcopenia in Older People and Asian Working Group for Sarcopenia criteria.MethodsWe systematically searched PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials up to July 2025. A Bayesian random-effects network meta-analysis was performed, with additional subgroup and meta-regression analyses. Certainty of evidence was assessed using the Confidence in Network Meta-Analysis (CINeMA) framework, and interventions were ranked according to their relative effectiveness and certainty of evidence. This study was registered in PROSPERO (CRD420251124534).ResultsA total of 35 randomised controlled trials involving 2,331 participants were included. Exercise combined with nutritional supplementation was the most effective intervention for improving handgrip strength (MD = 3.69, 95% CrI 0.72 to 5.10; SUCRA 99.04%), gait speed (MD = 0.11, 95% CrI 0.03 to 0.17; SUCRA 87.12%), and appendicular skeletal muscle mass index (ASMI) (MD = 0.35, 95% CrI 0.19 to 0.49; SUCRA 99.82%), with improvements in handgrip strength and ASMI significantly greater than those achieved with Exercise or Nutrition alone. Exercise alone improved handgrip strength, gait speed, and ASMI, whereas protein supplementation alone improved handgrip strength and gait speed but had no significant effect on ASMI. Subgroup analyses indicated that resistance training with protein supplementation produced the most significant improvements in handgrip strength and gait speed. In contrast, resistance training with protein and vitamin D supplementation was most effective for improving ASMI. Meta-regression analysis did not identify any significant sources of heterogeneity.ConclusionThese findings support combined exercise and nutritional interventions as a preferred treatment option for improving muscle strength, muscle mass, and physical function in older adults with sarcopenia. However, the overall certainty of the evidence ranged from low to very low. In particular, multicomponent exercise programmes centred on resistance training and combined with protein supplementation may offer superior benefits for enhancing muscle strength and physical function.